A full order observer-based guaranteed cost controller for uncertain linear systems. (27th October 2011) - Susanto, Erwin; Matsunaga, Daisuke; Ishitobi, Mitsuaki; Kunimatsu, Sadaaki
In this paper, a design scheme of a full order observer-based guaranteed cost controller for uncertain linear systems, in which all state variables cannot be known, is presented. The perturbations in system states and input are assumed to be described by structural uncertainties. An iterative linear matrix inequality (ILMI) approach is used to design the observer-based controller since the problems contain inverse relations. A numerical example is given to illustrate the proposed method.